2022
DOI: 10.1002/jcv2.12133
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics applied to child and adolescent mental health: Progress, challenges and opportunities

Abstract: Background: Epigenetic processes are fast emerging as a promising molecular system in the search for both biomarkers and mechanisms underlying human health and disease risk, including psychopathology. Methods:In this review, we discuss the application of epigenetics (specifically DNA methylation) to research in child and adolescent mental health, with a focus on the use of developmentally sensitive datasets, such as prospective, population-based cohorts. We look back at lessons learned to date, highlight curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 149 publications
(140 reference statements)
0
6
0
Order By: Relevance
“…We thus highlight the significance of epigenetic timing since, as mentioned above, alterations in epigenetic markers detectable at early stages can be transient and not measurable later in disease progression or life 48 , 74 . These timing effects could also explain some inconsistent findings reported in the literature 75 . We thus believe that the identification of early epigenetic biomarkers would be of relevance in order to predict disease trajectories and eventually choose a suitable therapy.…”
Section: Discussionmentioning
confidence: 87%
“…We thus highlight the significance of epigenetic timing since, as mentioned above, alterations in epigenetic markers detectable at early stages can be transient and not measurable later in disease progression or life 48 , 74 . These timing effects could also explain some inconsistent findings reported in the literature 75 . We thus believe that the identification of early epigenetic biomarkers would be of relevance in order to predict disease trajectories and eventually choose a suitable therapy.…”
Section: Discussionmentioning
confidence: 87%
“…Racial marginalization and low socioeconomic status has been associated with more advanced and faster biological aging as measured in DNAm in both adults and children, and, in adults, these differences in biological aging partially account for health disparities between and within racial groups (Del Toro et al, 2022; Oblak et al, 2021; Raffington et al, 2021; Sugden et al, 2023). A few studies have found DNAm measures of biological aging to be associated with mental health (Cecil et al, 2023; Oblak et al, 2021; Raffington, Tanksley, et al, 2023). Yet, previous research has largely been cross-sectional in design and, thus, does not address the dynamic interplay between racialization, mental health, and biological aging.…”
Section: Introductionmentioning
confidence: 99%
“…While making mechanistic inferences about the role of peripheral DNAm in brain‐based phenotypes is challenging (e.g. due to cross‐tissue variability in DNAm), research has increasingly demonstrated the potential of peripheral DNAm as a non‐causal biological marker for disease prediction, stratification, and diagnosis (Cecil, Neumann, & Walton, 2023 ; Min et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%